The influence of work environment, work ability, and affective commitment on performance management at kpspam, with work motivation as a mediating variable: a study in purworejo regency - Romadhonasari, Asih; Setyawati, Harini Abrilia (Jurnal Mantik, 2025)
This study aims to determine the influence environment work , ability work and commitment affective directly or through work motivation towards performance KPSPAM administrators in the Regency Purworejo. The independent variable in this study is the environment. work, ability work and commitment affective , the mediating variable is work motivation while the dependent variable is employee performance. The data collection technique in this study used a questionnaire to KPSPAM administrators in the Regency Purworejo totaling 159 respondents who were then analyzed using SEM using Smart PLS 3 .0. This study found that there was a significant influence of the environment work , ability work and commitment affective to work motivation and performance KPSPAM administrators in the Regency Purworejo . Motivation Work capable mediate influence environment work , ability work and commitment affective towards employee performance